Proper understanding of man as a basis for sustainable development: The anthropology of the Laudato si’ encyclical - Meller, Jacek (Studia Ecologiae et Bioethicae, 2019)
The fundamental reason for the contemporary ecological crisis is the current way of understanding of the human role in the world and the relationship between humans and the world. From the beginning of the modern period, anthropocentrism has appeared to be a leading idea, one which gives humans the right to meet their own needs at the expense of the environment, without limits. This idea, supported by modern concepts of science, liberty and economy, has justified overexploitation which destroys both the natural or social environment. Pope Francis, in the encyclical letter Laudato si’, urges the renewal of anthropocentrism rather than rejecting it. Its current form in Western culture, however, the pope calls a ‘tyrannical’ and ‘distorted’ anthropocentrism and calls to metanoia, to restore the attitude inherent in the Biblical idea of creation: man is to care about all the world, as God does.